Testing the waters meetings, retail trading, and capital market frictions - Alhusaini, Badryah; Chapman, Kimball L.; White, Hal D. (Review of Accounting Studies, 2025)
Abstract Pre-IPO firms may “test the waters” by meeting privately with investors in order to allow access to management and more time to make an investment decision. However, these meetings have the potential to undermine the SEC’s objectives of protecting investors and supporting market efficiency by allowing institutional investors, but not retail investors, private access to management. We find lower retail trading after IPOs of firms that held testing-the-waters meetings, consistent with the meetings reducing retail investor participation. Moreover, retail investors that still participate in the market in the presence of testing-the-waters meetings have inferior investment outcomes. Nonetheless, we find no evidence of lower overall market liquidity or slower price discovery following testing-the-waters meetings. In fact, we observe a reduction in stock return volatility. Overall our evidence suggests that, while testing-the-waters meetings may harm retail investors, there does not appear to be a negative impact on overall market function.